2019
DOI: 10.1371/journal.pone.0209993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of viruses associated with encephalitis in São Paulo, Brazil

Abstract: The objective of this study was to characterize the prevalence of viral encephalitis due to arbovirus infection of the Togaviridae and Flaviviridae families in São Paulo, Brazil. A total of 500 cerebrospinal fluid (CSF) samples collected between August 2012 and January 2013, from patients with symptoms of acute encephalitis were analyzed. Findings suggestive of viral encephalitis—elevations in cell concentration, glucose and total protein—were observed in 234 (46.8%) samples, designated as Group 1. The remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
(55 reference statements)
4
10
0
6
Order By: Relevance
“…Symptoms include intense headache and neurological alterations such as memory loss, disorientation and meningoencephalitis. Mortality rates in severe cases may reach up to 20% with possible sequelae to survivors [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms include intense headache and neurological alterations such as memory loss, disorientation and meningoencephalitis. Mortality rates in severe cases may reach up to 20% with possible sequelae to survivors [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before being reclassified as EV A‐D, EVs were originally classified as polioviruses 1 to 3, coxsackieviruses (CV) A1–24 and B1–6, echoviruses (E) 1 to 33, and numbered EVs (68‐121) 7 . Although EVs have long been recognized as the most common aseptic meningitis cause, 8 in Brazil they have been poorly characterized in CNS etiological studies, 9‐11 where only the genus Enterovirus was identified 12‐16 . Therefore, knowledge about specific EV genotypes circulating in CNS infections in the country remains sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Ao se analisar exclusivamente os dados provenientes do banco de dados brasileiro, o grupo com o maior número de óbitos foi o de adultos jovens (dos 20 aos 49 anos), e a partir dessa informação, é possível a criação de hipóteses do porquê o maior número de óbitos prevaleceu nesta faixa etária. Ao pensar que esse grupo é considerado jovem, saudável e economicamente ativo, chega-se na conclusão de que muitos indivíduos acabem por menosprezar os primeiros sintomas do quadro viral e por postergarem a procura por atendimento médico, visto que se tratam de sintomas mais brandos clássicos da encefalite viral, como febre e cefaleia (11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26).…”
Section: Discussionunclassified
“…Além disso, segundo os valores coletados todas as cinco regiões brasileiras apresentaram um dado semelhante, sendo ele o menor número de internações ocorrendo na faixa etária de 80 anos e mais, o que não é esclarecido na literatura. Porém, é plausível se atentar ao fato de que como a expectativa de vida da população brasileira ainda não se compara com a de países desenvolvidos, pode ocorrer que um menor número absoluto de idosos tenha como consequência, um menor número absoluto de internações em idosos com 80 anos e mais (11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26) Em relação aos resultados dos gráficos sobre a distribuição do número de óbitos por encefalite dentre as regiões brasileiras, é observado que as regiões com maior número de óbitos por encefalite viral são, em 1º lugar a região Nordeste com 439 óbitos (40,65% do total), e em 2º lugar a região Sudeste com 324 óbitos (30% do total). Ambas as regiões além de apresentarem os maiores números de óbitos no Brasil, também apresentaram números acima da média do total de óbitos de cada região dentre os anos de 2010 a 2019.…”
Section: Discussionunclassified